Exploring institutional arrangements for local fish product labelling in Tuscany (Italy): A convention theory perspective - Paolo Prosperi; Daniele Vergamini; Fabio Bartolini (Agricultural and Food Economics, 2020)
Increasing fish consumption along with rising competition in the global seafood market has brought fisheries and aquaculture producers to adopt several differentiation and marketing strategies. Labelling schemes were thus introduced to respond to a growing demand for traceable and sustainable products. However, the proliferation of quality labels brought to general confusion, calling for collective and public fish labels to ease decision-making. In our case study region (Tuscany, Italy), a number of policy-driven efforts were deployed for establishing regional labelling schemes for fisheries products with no observable impact on the market. Meanwhile, local companies have implemented a number of successful private and regional labels. The purpose of this research is to contribute to potential options for collective regional labelling schemes of fisheries and aquaculture products, through a case study analysis, building on agro-food value-chain and management approaches. Our empirical results highlight key issues and perspectives on labelling policies for local fisheries and aquaculture products.
Keywords: 330; Fisheries; Aquaculture; Value chain; Quality conventions; Primary producers; Vertical coordination; Eco-labels; Sustainability certifications